2015
DOI: 10.1124/jpet.115.227587
|View full text |Cite
|
Sign up to set email alerts
|

MLi-2, a Potent, Selective, and Centrally Active Compound for Exploring the Therapeutic Potential and Safety of LRRK2 Kinase Inhibition

Abstract: Mutations in the leucine-rich repeat kinase 2 (LRRK2) gene are the most common genetic cause of familial and sporadic Parkinson's disease (PD). That the most prevalent mutation, G2019S, leads to increased kinase activity has led to a concerted effort to identify LRRK2 kinase inhibitors as a potential disease-modifying therapy for PD. An internal medicinal chemistry effort identified several potent and highly selective compounds with favorable drug-like properties. Here, we characterize the pharmacological prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
307
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(331 citation statements)
references
References 32 publications
15
307
0
Order By: Relevance
“…LRRK2 phosphorylation induced a time-dependent retardation in the migration of phosphorylated Rab10, an effect that was prevented by inclusion of the MLi-2 LRRK2 kinase inhibitor in the kinase reaction [36] (Figure 1A). Immunoblot analysis with a phospho-specific antibody confirmed that the slower migrating Rab10 species that appears following LRRK2 phosphorylation is indeed Rab10 phosphorylated at Thr 73 (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…LRRK2 phosphorylation induced a time-dependent retardation in the migration of phosphorylated Rab10, an effect that was prevented by inclusion of the MLi-2 LRRK2 kinase inhibitor in the kinase reaction [36] (Figure 1A). Immunoblot analysis with a phospho-specific antibody confirmed that the slower migrating Rab10 species that appears following LRRK2 phosphorylation is indeed Rab10 phosphorylated at Thr 73 (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, LRRK2 knockouts are not protected from the mitochondrial complex I inhibitor MPP that is selectively internalized in DAT-1 expressing neurons(Andres-Mateos et al, 2009). Protection was also not recorded in mice treated with a LRRK2 kinase inhibitor in the MitoPark mice that have neurodegeneration caused by mitochondrial deficits in DAT-1 expressing neurons(Fell et al, 2015). Thus, from these studies it can be deduced that neuroprotection associated with LRRK2 inhibition may be due to reductions in neuroinflammation, potentially related to the damaging effects of wild-type α-synuclein over-expression.…”
Section: Evidence For Lrrk2 Kinase Inhibition In Neuroprotectionmentioning
confidence: 99%
“…Chronic oral dosing of both rats and mice with third-generation LRRK2 kinase inhibitors has been described for the MLi-2 compound, as well as for the PFE475 compound(Daher et al, 2015; Fell et al, 2015). In these studies, dosing that achieved near-continuous brain LRRK2 inhibition (up to 90% inhibition for much of the day) did not produce clear phenotypes associated with the LRRK2 knockout in rodents, and only mild or non-significant effects on reducing total LRRK2 protein.…”
Section: Safety Of Lrrk2 Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its ability to inhibit LRRK2 in vivo reveals that it can cross the BBB. Since its description in 2012, several novel, selective, and brain-penetrating LRRK2 inhibitors have been described, including ­GSK2578215A [60], GNE-7915 [61], JH-II-127 [62], ­PF-06447475 [63], and MLi-2 (Table 1 for further details) [64]. These next-generation LRRK2 inhibitors exhibit improved potency, selectivity, and brain penetrability, all of which are important for clinical application.…”
Section: Lrrk2 As a Therapeutic Targetmentioning
confidence: 99%